ACTUALISATION STRUCTURALE DE L’AQUIFÈRE DU PALÉOCÈNE DANS LE BASSIN CÔTIER DU TOGO - Gnazou M.D.T.; Sabi B. E.; Togbe K.A.; da Costa Y.D.; Agouda, K (European Scientific Journal, ESJ, 2015)
Groundwater is one of the main sources of drinking water to the population living in the coastal sedimentary basin of Togo. Faced with the depletion and pollution of the most accessible aquifer of the Continental terminal, it is important to find alternatives groundwater resources, exploring the potential of the deep aquifers that are little exploited this day. This study aims to improve knowledge of one of these deep aquifers and particularly the Paleocene aquifer. The Paleocene aquifer is a confined aquifer and this study focuses on its configuration, its location and its structure, based on the systematic inventory of wells and stratigraphy. Thus geological sections of North-South and West-East directions have allowed knowing the extent and geometry of this aquifer, as well as the nature of the reservoir and wall rocks. They also show that the sedimentary formations of coastal basin are organized in a monocline series dipping toward south. Different results were represented as isopach map of the reservoir and isohypse maps of upper confining bed and lower confining one. As the others formations of the basin, the wall rocks take on an air of an inclined plane towards the Atlantic Ocean. The upper confining bed elevations range from 20 m in the northern part of the basin, at -380 in the Southeast. Those of lower confining bed in the same sectors are 0 in NW and -20m in NE at -420 m in the South. This morphology of the aquifer is related to the NNW-SSE direction of extension faults that affected the crystalline basement at the opening of the Atlantic Ocean. Estimates of the reservoir thickness are between 6m to more than 50 m and are influenced by the base sands.